Note on real and monetary effects of an exogenous change in interest rates - Honohan, P (Economic & Social Studies, 1974)
The interesting article by D. Rodney Thom (Economic and Social Review, January 1974) seems to contain a misleading assertion which makes his statistical results difficult to interpret. Thom's main thesis is that, in the Irish situation, the result of a change in the (exogenously determined) level of interest rates can be decomposed into 'monetary' and 'real' effects working in opposite directions, for example, an expansionary 'monetary'1 and a contractionary 'real' effect following a rise in interest rates.
Keywords: Interest Rates; Ireland